Prevalence of Burnout Syndrome in Principals of Public Educational Institutions in Barrios Altos, Lima, Perú - De la Guerra-De Urioste, Juan Pablo (2021)
Objective. This research aims to determine the prevalence of burnout syndrome in principals of regular basic education institutions in Barrios Altos, Lima. Method. A non-experimental research design was used, with a descriptive orientation of the study event, for which the Maslach Burnout Inventory was applied to 22 principals from a management team of public educational institutions, which constitute 100% of the study population. Results. A medium level of emotional exhaustion, a low level of depersonalization, and highly personal accomplishment have been found. Conclusions. The prevalence of burnout syndrome in the group of principals is low, but moderate levels of exhaustion are found emotional, which are a feature that, if maintained over time, could lead to burnout. This work constitutes a preliminary research contribution, leaving the way for future studies related to school management and burnout syndrome.